Peningkatan Gain Antena Mikrostrip Patch Rectangular dengan Metode Element Parasitic Pada Frekuensi 2.1 GHz - Wira Indani; Jhones Rona Sembiring (Politeknik Caltex Riau, 2020)
The development of the world of wireless telecommunications is quite rapid, this is because the mobility of people who are increasingly demanding to move and move always, and dependence on communication media is quite high. One of the most influential devices in wireless media is an antenna. Where in this paper will discuss the design of a microstrip antenna in order to increase the gain using the parasitic element method and the iteration technique of the slot position with the rectangular slot to increase the return loss value on the antenna. For the type of substrate used is FR-4 Epoxy with h = 1.6 mm ε_r = 4.6 and the feeding technique used is the microstrip line. From the research results, it was found that adding parasitic techniques to the antenna was able to produce a gain twice as large as without parasitic elements. In addition, when the state is added the slot position iteration technique is able to produce a better return loss value than the patch optimization state. So that the optimal results are obtained on a single band 2.1 GHz antenna with a return loss of -13.20 dB VSWR 1.53 impedance 50.44 Ω and a gain of 4.79 dB.